Thermal barrier coatings for gas turbine applications: failure mechanisms and key microstructural features (2012)
Advances in new materials for current power generation devices, such as gas turbines, have led to more efficient and durable engines that supply rising energy demands. High efficiencies in gas turbines, due to higher operating temperatures, have been accomplished through the development of thermal barrier coatings. These are multilayered systems that provide thermal isolation capability and protection against corrosion and high temperature erosion. In this work, we describe the barrier’s application processes, their microstructural characteristics and their main failure mechanisms. Two different thermal barrier coatings are characterized and the most relevant trends of these systems are summarized.